2022
DOI: 10.21608/tsnj.2022.221551
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Protocol of Hygienic Care by Chlorhexidine Gluconate on the Occurrence of Catheter Associated Urinary Tract Infection among Critical Ill Patients

Abstract: Catheter-associated urinary tract infections (CAUTIs) is the most common type of hospital acquired infection in Intensive Care Units. It is associated with significant morbidity, length of hospital stay and cost of hospitalization. Preventing CAUTI is essential and critical care nnurses are the key to accomplishing this goal. Aim: -evaluate the efficacy of protocol of hygienic care by chlorhexidine gluconate on the occurrence of a catheter associated urinary tract infection among critically ill patients. Desgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…As regards gender, the present study found that the majority of the IG was males. The present study finding contradicted (Omer et al, 2020) [13], who revealed that a minority of the patients were male. In addition, the study by (Chandna, Pandey, and Maheshwari, 2022) [12] reported that more than one-third of the population was male.…”
Section: Discussioncontrasting
confidence: 99%
“…As regards gender, the present study found that the majority of the IG was males. The present study finding contradicted (Omer et al, 2020) [13], who revealed that a minority of the patients were male. In addition, the study by (Chandna, Pandey, and Maheshwari, 2022) [12] reported that more than one-third of the population was male.…”
Section: Discussioncontrasting
confidence: 99%